Design, synthesis, spectroscopic characterizations, in vitro pancreatic lipase as well as tyrosinase inhibition evaluations and in silico analysis of novel aryl sulfonate-naphthalene hybrids - Korkmaz, Adem; Kurtay, Gülbin; Kaya, Esin; Bursal, Ercan (Taylor & Francis Inc, 2022)
One of the primary purposes of this study is to synthesize new aryl sulfonate-naphthalene hybrid structures possessing divergent electron-withdrawing and electron-releasing functional groups. Following the improved reaction conditions, we successfully gathered ten distinct sulfonate derivatives (3a-j) with good yields. The synthesized naphthalene-based sulfonate derivatives were then characterized using appropriate analytical methods (FT-IR, H-1-NMR, C-13-NMR, HRMS, and elemental analysis). Additionally, in vitro and in silico enzyme inhibitory properties of the prepared aryl sulfonate-naphthalene hybrid structures were evaluated against pancreatic lipase and tyrosinase enzymes. Corresponding in vitro enzyme activity investigations revealed that the produced compounds inhibit pancreatic lipase and tyrosinase enzymes significantly. According to the lowest IC50 values, 3h (95.3 +/- 4.0 mu M) demonstrated the most effective inhibition against pancreatic lipase, whereas 3a (40.8 +/- 3.3 mu M) was found as the most effective inhibition against the tyrosinase. According to in silico studies, 3a exhibited the highest affinity value (-9.9 kcal/mol) against pancreatic lipase, whereas 3f demonstrated the best affinity value (-8.7 kcal/mol) against tyrosinase. Furthermore, we investigated various structural and physicochemical properties of the target molecules, namely frontier orbital' (HOMO, LUMO, and bandgap) energies (including their corresponding contour plots), global reactivity descriptors (ionization energy and electron affinity), and electronegativity values gathered from ground-state (GS) density functional theory (DFT) calculations. These investigations demonstrated that the observed electrostatic interactions effectively contributed to the studied molecules' experimentally demonstrated enzyme inhibition potential. Also, ADMET studies were evaluated to enlighten the molecular interactions of the compounds with the enzymes. Communicated by Ramaswamy H. Sarma
Keywords: Enzyme inhibition; molecular docking; naphthalene-based sulfonate derivatives; pancreatic lipase; tyrosinase; Biological Evaluation; Molecular Docking; Derivatives